KESADARAN HUKUM MASYARAKAT TERHADAP PERCERAIAN DI PENGADILAN: Studi Masyarakat Desa Tangkil Tengah Terhadap Perceraian di Luar Pengadilan Atas Dasar Pelanggaran Taklik Talak - Salamah, Aghniya; Diniyanto, Diniyanto (Al-Hukkam: Journal of Islamic Family Law, 2023)
This study found the causes of the community carrying out divorces and the legal awareness of the Muslim community in the Tangkil-Tengah village of divorce outside the court on the basis of taklik talak violations. Through juridical- sociological research with a qualitative approach to legal awareness theory. The research data were obtained through purposive interviews, observation and documentation. The results of this study indicate that: (1) the factors causing out- of-court divorces conducted by the people of Tangkil Tengah Village are internal factors, namely economic factors, busy factors, and a factor of lack of understanding about the legal consequences of divorce. And external factors, namely the lack of socialization from legal institutions regarding procedures for registering marriages, legal divorce and state legality. (2) The legal awareness of the Muslim community in Tangkil Tengah Village regarding divorce outside the court on the basis of a violation of taklik talak seen from the indicator of legal awareness found that in fact the legal awareness of the Muslim community in the village of Tangkil Tengah who divorced outside the court is still relatively low, where they have knowledge and understanding regarding divorce must be before a Court hearing, but do not do so. Their attitudes and behavior patterns actually ignore and do not comply with divorce procedures based on positive law in Indonesia. This makes the legal system not fully effective in society.